The Concept of Islamic Aesthetic of Abdul Hadi WM - Siraj, Fuad Mahbub; Alrah, Zikraini (KALAM, 2022)
This study aims to see how the concept of Islamic aesthetics in the thought of Abdul Hadi WM. Aesthetics is an interesting discourse to study because aesthetics is one of the five branches of philosophy that relate to values that are contained in something or arise from human actions. Although the values contained in aesthetics are very important and are always relevant in human life, the fact is that aesthetics receive less attention in philosophical studies. One reason is the narrow view that aesthetics is only related to art. Abdul Hadi WM sees an important aesthetic in the realm of philosophy and is related to human aesthetic experience. Islamic aesthetics essentially refers to the expression of religious values and can bring awareness to the spiritual realm